Enhancement of callogenesis from plumular explants of coconut (Cocos nucifera) via exogenous supplementation of amino acids and casein hydrolysate (Current Horticulture, 2024)
The role of exogenous supplementation of amino acids and casein hydrolysate in enhancing callogenesis from plumular explants of coconut (Cocos nucifera L.) was studied at ICAR-Central Plantation Crops Research Institute, Kasaragod, Kerala, during 2020-21. The combination of three amino acids, viz. glutamine, asparagine, proline, and organic additive casein hydrolysate were supplemented in three types of basal media (Eeuwen's Y3, Murashige and Skoog (MS) and 1/2MS) containing 2, 4-D (16.5 mg/L), charcoal (0.1%) sucrose (3%) and agar (0.8%). A total of 19 treatments were formulated and tested for production of embryogenic colloid tissue. The explants in glutamine-supplemented medium generated better colloid tissue and showed positive effect on colloid tissue multiplication, compared to other combinations. Of three basal media, Y3 was better over 1/2MS and MS basal media. These results could be useful for improving the efficiency of in-vitro regeneration in coconut by somatic embryogenesis from plumular explants.
Keywords: Embryogenic calli; Amino acids; Basal media; Plumule; Callogenesis; Explants